(untitled) (Research, Society and Development, 2022)
Fish is the main source of food for the population of Tabatinga, who have six points of sale in the municipality. Describing the hygienic and sanitary conditions, fish quality and commercialized species were the objectives of this study. The “in loco” visits took place between August 2016 and July 2018 through observations and periodic surveys. Five orders, 17 families and 86 species traded in Tabatinga were identified. It was found that 67% are sold in natura, 29% cooled, 2% frozen, 1% dry salted and 1% salted. Basic structure such as isothermal boxes, utensils, chlorinated water and ice by traders is a problem in terms of hygiene and sanitation. In two places they have poor hygienic and sanitary conditions and there is no recommendation for buying fish, in two places they are public, and improvements were observed, but there is a need for handling training for traders, there is a private point with farmed fish and another without physical structure, but with the option of a new indigenous fair. The most suitable fish for consumption were found in vendors who store in isothermal boxes with ice in a 1:1 ratio, using water to clean the environment and utensils. We recommend not buying fish at ambient temperatures, exposed to dust, sun and close to streets. There is a need to guide consumers on the choice of quality fish for consumption. Complementary studies are needed for a microbiological and physicochemical evaluation to determine the quality of the fish.